2021
DOI: 10.3389/feduc.2021.770710
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship Perceptions on Entrepreneurial Intention During the COVID-19 Pandemic

Abstract: The global pandemic of COVID-19 is a challenge for entrepreneurship education in universities and various organizations. Although positive responses to overcome the challenges of COVID-19 are being made, entrepreneurship strategies and policies might not meet students’ requirements. In order to enrich education management research, the main aim of this study is to provide a conceptual model and examine the relationship between perceptions, perceived positive attitudes on entrepreneurship education, and entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…Arve et al [5]'s findings underline the profound effect of external uncertainties by depicting the lockdown's catastrophic impact on entrepreneurial intentions and resilience. Similarly, as observed by [23], the uncertainty of COVID-19 acts as a resistant force against entrepreneurial intentions and hinders the entrepreneurial decision-making process. The collective findings underscore across diverse contexts the nuanced and multifaceted nature of the relationship between the uncertainty of COVID-19 and entrepreneurial intentions.…”
Section: Uncertainty Of Covid-19 Entrepreneurial Intention and Busine...mentioning
confidence: 65%
See 2 more Smart Citations
“…Arve et al [5]'s findings underline the profound effect of external uncertainties by depicting the lockdown's catastrophic impact on entrepreneurial intentions and resilience. Similarly, as observed by [23], the uncertainty of COVID-19 acts as a resistant force against entrepreneurial intentions and hinders the entrepreneurial decision-making process. The collective findings underscore across diverse contexts the nuanced and multifaceted nature of the relationship between the uncertainty of COVID-19 and entrepreneurial intentions.…”
Section: Uncertainty Of Covid-19 Entrepreneurial Intention and Busine...mentioning
confidence: 65%
“…The tremendous impact of external uncertainty is depicted in the findings of [5], which describe the lockdown's disastrous impacts on entrepreneurial intentions and resilience. Similarly, uncertainty about COVID-19 is a barrier to entrepreneurial intentions, impeding the decision-making process [23]. The combined results highlight in various settings the complex and varied relationship between the uncertainty of COVID-19 and entrepreneurial intentions.…”
Section: Uncertainty Of Covid-19mentioning
confidence: 84%
See 1 more Smart Citation
“…Several authors have shown the effect of entrepreneurial intention from various perspectives (Trivedo, 2016); Li et al (2021a) found in Chinese university students that entrepreneurial intention provides theoretical evidence to support the foundations of education and culture of entrepreneurship. Likewise, other studies have found that elements such as education and knowledge are crucial to strengthening entrepreneurial intention in university students, which contributes to the economic growth of regions, including in critical stages such as post-COVID-19 (Li et al, 2021b;Wang et al, 2021;Engidaw, 2021).…”
Section: Entrepreneurial Intentionmentioning
confidence: 95%
“…If a person is facing continuous threat to his life and belongings, he can never develop any kind of positive intentions within himself. More precisely, Li et al, (2021), have proposed that if the available resources of human being are under threat, due to that perception of threat they never develop intention or make-up their mind to entrepreneurial intentions. This connection of entrepreneurial intentions with threat of terrorism can be elaborated through discussing the conservation of resource theory as mentioned below;…”
Section: Literature Reviewmentioning
confidence: 99%